Avaliação da atividade antimicrobiana do extrato etanólico da casca do caule do uxir amarelo Endopleura uchi (Huber) cuatrec. Contra bactérias de importância médica - Penedo, Danyelle valery gomes (Brasil, 2022)
The search for herbal medicinal plants has become increasingly frequent, as they harm health less when compared to synthetic drugs. Because some plant species are an important source of medicines. The main objective of this project was to evaluate the antimicrobial activity of the ethanolic extract of the stem bark of Endopleura uchi (Uxir Amarelo) against bacteria of medical importance and to perform a preliminary phytochemical screening of the extract. The plant material was purchased commercially, then subjected to extraction by the cold maceration method. Preliminary phytochemical screening was performed using colorimetry. The disk diffusion method was used to evaluate the antimicrobial activity of the ethanolic extract of the stem bark of E. uchi. The extract yield was 21.2g. The following classes of metabolites identified in the preliminary phytochemical screening were: saponins, tannins, flavonones, flavonones, anthocyanins, anthocyanidins, quinones and leucoanthocyanidins. The results of the inhibition halos of the ethanol extract of the stem bark of E. uchi against the bacteria were (Shigella flexneri [750mg/mL] = 9.66mm, [850mg/mL] =10.33mm, [950mg/mL]=11.00mm ), and Enterococcus faecalis ([750 mg/mL]=10.66mm; [850mg/mL]=10.88mm; [950mg/mL]=11.88mm). The bacterium Pseudomonas aeruginosa did not show inhibition halos of the extract. Therefore, it was possible to notice the potential of the antimicrobial activity of the stem bark of the yellow uxir against bacteria of medical importance, which makes this topic relevant for scientific research. Thus contributing to the appreciation of this species through the dissemination of its biological activity. I believe that this work can contribute to biotechnological science, but further studies are needed. Keywords: Natural antibacterial, Medicinal plant, Endopleura uchi.